Construction and tissue regeneration evaluation for mature chondrocyte/scaffold complex under optimal compression loading. (December 2022) - Lin, Xianglong; Gao, Lilan; Li, Kai; Zhang, Chunqiu; Li, Ruixin; Tan, Yansong; Zhang, Xizheng
Graphical abstract: Abstract: The tissue engineering is a promising method for cartilage regeneration studies. The rough in vivo initial repair environment of articular cartilage is a challenge for the development of cartilage tissue engineering. Hereon, in this study, a silk fibroin/collagen type II scaffold was designed. The optimal mechanical environment for chondrocyte/scaffold complex in vitro maturation culture was determined and in vitro cultured mature artificial cartilage was evaluated for in vivo defect repair. Our research shows that the silk fibroin/collagen type II scaffold has good performance and can meet the special requirements of cartilage repair. 10 % compressive strain is the optimal compressive loading in vitro . Under optimal compression loading in vitro, chondrocytes can proliferate and grow rapidly on the scaffold to achieve better "maturation". The in vitro cultured chondrocyte/scaffold complex effectively improves the cartilage repair effect after implantation. The compressive elastic modulus of the new tissue reached 0.682 ± 0.010 MPa after 12 weeks of repair (0.714 ± 0.011 MPa for the surrounding host cartilage). Therefore, this study not only enhance the effect of cartilage repair but also provides a promising strategy for mechanical stimulation to promote functional in situ regeneration of articular cartilage.